The correlation between the melting point and the chemical composition of the ash generated in thermal power plant in South-Brazil Estudo da correlação entre a temperatura de fusão e composição química das cinzas gerada em usina termelétrica no Sul do Brasil - Joao J.J. (2017)
In this work, a study of the relationship between the chemical composition and the melting temperature of the ash produced by burning coal in boilers. The analytical methodology applied for the oxides determination in the ashes was the X-rays fluorescence. The melting point was assessed using a heating microscope with automatic image analysis. The obtained data were correlated using linear and nonlinear models, with factors such as the chemical composition of the ashes and in response to melting temperature. The nonlinear model showed a higher correlation between the data related to the deformation, hemisphere and flow temperature. However, a linear model was the best model to describe the sphere temperature. The results revealed that the chemical composition of the ash influences its melting temperature, and this information can be applied in the management of the units to control the quality of the coal used in boilers.